Influence of an individual's age on the amount and interpretability of DNA left on touched items - Poetsch, Micaela; Bajanowski, Thomas; Kamphausen, Thomas (International Journal of Legal Medicine, 2013)
In crime scene investigations, DNA left by touch on an object can be found frequently and the significant improvements in short tandem repeat (STR) amplification in recent years built up a high expectation to identify the individual(s) who touched the object by their DNA profile. Nevertheless, the percentage of reliably analysable samples varies considerably between different crime scenes even if the nature of the stains appears to be very similar. Here, it has been proposed that the amount and quality of DNA left at a crime scene may be influenced by external factors (like nature of the surface) and/or individual factors (like skin conditions). In this study, the influence of the age of an individual who left his DNA on an object is investigated. Handprints from 213 individuals (1 to 89 years old) left on a plastic syringe were analysed for DNA amount and STR alleles using Quantifiler® and PowerPlex® ESX 17. A full profile of the individual could be found in 75 % of all children up to 10 years, 9 % of adolescents (11 to 20 years), 25 % of adults (21 to 60 years) and 8 % of elderly people (older than 60 years). No person older than 80 years displayed a full profile. Drop-in and drop-out artefacts occurred frequently throughout the age groups. A dependency of quantity and quality of the DNA left on a touched object on the age of the individual could be clearly demonstrated at least for children and elderly people. An epithelial abrasion unexpectedly good to interpret may be derived from a child, whereas the suspected skin contact of an elderly person with an object may be impossible to prove. © 2013 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Age; Crime scene investigation; Low copy number DNA; STR